Angiographic Complete versus Clinical Selective Incomplete Percutaneous Revascularization in Heart Failure Patients with Multivessel Coronary Disease - Chieh-Yu Chang; Chun-Chi Chen; I-Chang Hsieh; Ming-Jer Hsieh; Cheng-Hung Lee; Dong-Yi Chen; Ming-Lung Tsai; Ming-Yun Ho; Jih-Kai Yeh; Yu-Chang Huang; Yu-Ying Lu; Chao-Yung Wang; et al. (Journal of Interventional Cardiology)
Background. Patients with multivessel disease (MVD) often pursue complete revascularization (CR) during percutaneous coronary intervention (PCI) to improve prognosis. However, angiographic CR is not always feasible and is associated with some procedure-related complications in heart failure (HF) patients with MVD. Clinical selective incomplete revascularization (IR) may be reasonable for these high-risk patients, but its role in long-term outcomes remains uncertain. Methods. Six hundred patients with HF and MVD submitted to PCI were enrolled. Major adverse cardiac events (MACEs) were defined as a composite of recurrent myocardial infarction, any revascularization, and all-cause mortality at 5 years. Results. During a mean follow-up period of 3.7 ± 1.9 years, there was no significant difference in 5-year MACEs between selective IR and successful angiographic CR in HF patients with MVD. However, patients who failed CR had a significantly greater incidence of 5-year MACEs than those in the other two groups (failed CR: 46.4% vs. selective IR: 27.7% vs. successful CR: 27.8%, p<0.001). Conclusions. Long-term outcomes of selective IR were comparable with those of successful angiographic CR in HF patients with MVD. However, patients that failed CR showed 2.53-fold increased risk of MACEs compared to patients undergoing either selective IR or successful angiographic CR. A more comprehensive planning strategy should be devised before PCI in HF patients with MVD.